Heat Transfer Analysis of Laboratory Scale Reactor of Fast Pyrolysis Fluidised Bed - Tan, Yong Sin (2015)
This report presents the results of heat transfer analysis of a fluidised bed by using different type of fluidised bed sands. Academic version of FLUENT 15.0 was used in performing the simulations. Eulerian-Eulerian two-fluid granular model is used as the multiphase flow model to solve this simulation. 2-D axisymmetric fluidised bed (2.5cm X 50cm), glass beads and stainless steel beads of 1 mm and 0.5mm in diameter are used in the simulations. Thermal conductivity of the material is calculated using the standard approach used by Kuipers et al. (1992). Gidaspow model is used for the drag equation and Gunn’s model (1978) is used in the calculation fir interphase heal transfer coefficient.